Pengelolaan Sampah Plastik Menggunakan Teknik Ecobrick Sebagai Upaya Pendidikan Sadar Lingkungan di Madrasah Ibtidaiyah Al-Huda Sidoarjo - Adam Rayhansyah; Enjelly T. Callista; Herawati T. Rongko; Hilmy Y. Ramadhani; Gita W. Ningsih; Puteri N. Wulan; Riska N. Khaula; Shinta Mahmudah; Tukiman Tukiman (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Currently, Indonesia is ranked fifth as the country that contributes the most plastic waste in the world. Waste management, especially plastic waste, is currently still relatively low. Plastic waste that is not managed properly can cause environmental pollution and habitat destruction. The solution to this problem is to create new innovations using ecobrick techniques. Ecobrick is a technique for utilizing plastic waste into useful items and reducing the amount of plastic waste. The purpose of this service is to increase environmental awareness from an early age, especially for grade 4 students of Madrasah Ibtidaiyah Al-Huda Sidoarjo. The methods used are socialization of waste management and the practice of making and handing over ecobrick products. The results obtained are that students can understand the importance of maintaining environmental cleanliness by sorting waste according to its type, and can make useful ecobrick products.